Phenotypic variation within European carriers of the Y-chromosomal gr/gr deletion is independent of Y-chromosomal background. Issue 1 (9th September 2008) - Krausz, C; Giachini, C; Xue, Y; O'Bryan, M K; Gromoll, J; Meyts, E Rajpert-de; Oliva, R; Aknin-Seifer, I; Erdei, E; Jorgensen, N; Simoni, M; Ballescà, J L; et al.
Abstract : Background: Previous studies have compared sperm phenotypes between men with partial deletions within the AZF c region of the Y chromosome and non-carriers, with variable results. In this study, a separate question was investigated, the basis of the variation in sperm phenotype within gr/gr deletion carriers, which ranges from normozoospermia to azoospermia. Differences in the genes removed by independent gr/gr deletions, the occurrence of subsequent duplications or the presence of linked modifying variants elsewhere on the chromosome have been suggested as possible causal factors. This study set out to test these possibilities in a large sample of gr/gr deletion carriers with known phenotypes spanning the complete range. Results: In total, 169 men diagnosed with gr/gr deletions from six centres in Europe and one in Australia were studied. The DAZ and CDY1 copies retained, the presence or absence of duplications and the Y-chromosomal haplogroup were characterised. Although the study had good power to detect factors that accounted for ⩾5.5% of the variation in sperm concentration, no such factor was found. A negative effect of gr/gr deletions followed by b2/b4 duplication was found within the normospermic group, which remains to be further explored in a larger study population. Finally, significant geographical differences in the frequency of different subtypes of gr/gr deletions were found, which may have relevance for the interpretation of case control studies dealing with admixed populations. Conclusions: The phenotypic variation of gr/gr carriers in men of European origin is largely independent of the Y-chromosomal background.